The impact of China’s Belt and Road Initiative on the Western Balkan Region: An erosion of EU conditionality? - Cotella, Giancarlo; Berisha, Erblin (European Spatial Research and Policy, 2021)
The EU integration process contributes to influence the ongoing institutional changes in the Western Balkans. At the same time, the incremental inflow of Chinese capital in the region that followed the launch of the Belt and Road Initiative is progressively reshaping power relations there. This article sheds light on the interaction between these two processes, discussing whether the increasing inflow of resources may gradually erode EU conditionality and hinder the overall integration process. To do so, the authors draw on an extensive review of academic and policy documents and on selected expert interviews, upon which they compare the actions of the EU and China in the region.